Adaptive Tutoring System untuk Pembelajaran Bahasa Pemrograman di Universitas Stikubank Semarang - Muji Sukur; Saefurrohman Saefurrohman; Setyawan Wibisono (Universitas Stikubank, 2010)
This research made for applying adaptive tutoring system for programming languages learning.Adaptive tutoring system that developed have ability to present learning material, providing quiz problem,test problem and pretest. System has ability to present learning material accords ably student materialmastery. Material representation bases prerequisite material probability that accounted by bayes'stheorem, meanwhile student material mastery is accounted bases time that is utilized to study material,assess quiz that is reached and student test point. Developed system gets web basis to be able to beaccessed by a lot of student on one time and learning get at call been done. In this research is concludedthat adaptive tutoring system can help student does navigation learning material, recommending learningaim and presents learning material thread.